Implicit Incentives in International Joint Ventures An Experimental Study - Wu, Fan.; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Managers in international joint ventures work with resources contributed by investors from multiple nationalities. Fan Wu shows through a series of experimental studies among students and managers from China, South Korea, Germany, and the USA that cultural affinity between the manager and one of the investors and career perspectives with one of the investors are strongly motivating managers to make biased decisions. The two mechanisms can be used to balance each other out in staffing key positions in international joint ventures for optimal control over managerial decisions.
Keywords: Economics; Economics/Management Science; Business Strategy/Leadership.